Translation quality control is critical for bacterial responses to amino acid stress - Bullwinkle, Tammy J. (Proc Natl Acad Sci U S A, 2016)
Gene expression relies on quality control for accurate transmission of genetic information. One mechanism that prevents amino acid misincorporation errors during translation is editing of misacylated tRNAs by aminoacyl-tRNA synthetases. In the absence of editing, growth is limited upon exposure to excess noncognate amino acid substrates and other stresses, but whether these physiological effects result solely from mistranslation remains unclear. To explore if translation quality control influences cellular processes other than protein synthesis, an Escherichia coli strain defective in Tyr-tRNA(Phe) editing was used. In the absence of editing, cellular levels of aminoacylated tRNA(Phe) were elevated during amino acid stress, whereas in the wild-type strain these levels declined under the same growth conditions. In the editing-defective strain, increased levels of aminoacylated tRNA(Phe) led to continued synthesis of the PheL leader peptide and attenuation of pheA transcription under amino acid stress. Consequently, in the absence of editing, activation of the phenylalanine biosynthetic operon becomes less responsive to phenylalanine limitation. In addition to raising aminoacylated tRNA levels, the absence of editing lowered the amount of deacylated tRNA(Phe) in the cell. This reduction in deacylated tRNA was accompanied by decreased synthesis of the second messenger guanosine tetraphosphate and limited induction of stringent response-dependent gene expression in editing-defective cells during amino acid stress. These data show that a single quality-control mechanism, the editing of misacylated aminoacyl-tRNAs, provides a critical checkpoint both for maintaining the accuracy of translation and for determining the sensitivity of transcriptional responses to amino acid stress.